Agroecological passport of the Marusya green bean variety - N. G. Kazydub; O. A. Kotsyubinskaya; A. N. Kovalenko (Овощи России, 2022)
Relevance. As a result of long-term research, the staff of the Department of Agronomy, Plant Breeding and Seed Production of Omsk State Agrarian University created a new variety of green beans called Marusya, which was included in the State Register of Breeding Achievements in 2015. The competitiveness of the variety is ensured by stable yields, high palatability, and the ability of green beans to maintain their economic viability over the long period. The variety is resistant to drought and low temperatures.Material and methods. The research on the variety of the green beans was conducted following the methods of competitive variety trial from 2016 to 2020. The trials were conducted on the breeding crop rotation fields of the Educational and Experimental Farm of Omsk State Agrarian University, which is located in the southern forest-steppe of the Omsk Region (city of Omsk). The following zoned varieties were used as control samples: Zolushka (Federal Scientific Center of Vegetable Farming, Moscow) and the imported Polka variety (Poland).Results. The developed agroecological passport the Marusya variety, the use of which will allow to take into account the positive effects of the genotype-environment-variety interaction to the maximum extent. When selecting bean varieties suitable for cultivation for vegetable purposes in the conditions of the southern forest-steppe of Western Siberia in industrial production and the private sector, the Marusya variety makes it possible to obtain high-quality products and expand the range of legumes in the region.